A phase II study of 9-nitrocamptothecin in patients with advanced pancreatic adenocarcinoma. - M Konstadoulakis, M; Antonakis, P T; Tsibloulis, B G; Stathopoulos, G. P.; Manouras, A P; Mylonaki, D B; Golematis, B X (Cancer Chemother Pharmacol, 2001)
PURPOSE: Preclinical and phase I clinical data suggest that 9-nitrocamptothecin (9NC) is an agent with potential anticancer activity. A phase II study was undertaken in order to evaluate the potential benefit of oral 9NC administration in patients with advanced pancreatic cancer. This was the first clinical study of 9NC in Europe. METHODS: A total of 19 consecutive patients with locally advanced or metastatic adenocarcinoma were enrolled (8 males and 11 females, aged 37-73 years). The patients were given 9NC orally five times a week, once a day. The end-points of this study were toxicity, objective response rate, subjective response rate (i.e. pain control, performance status and body weight), and survival. RESULTS: An objective response was documented in 4 of the 14 evaluable patients (28.6%), while a subjective response was observed in 13 patients (92.9%). Overall median survival was 21 weeks (31 weeks in the group of 14 patients evaluable for response), and the 1-year survival was 16.7% and 23.1%, respectively. Toxicity leading to temporary discontinuation of 9NC was encountered in seven patients (36.8%), all related to a prior dose increase, while milder toxicity was observed in eight patients (42.1%). CONCLUSIONS: 9NC administered orally to patients with advanced pancreatic cancer gave promising results, while the toxicity of the therapy was mild and readily overcome. A larger scale clinical trial should be organized in order to establish the potential benefit of 9NC in patients with pancreatic adenocarcinoma.
Keywords: Adenocarcinoma; Adult; Aged; Antineoplastic Agents; Camptothecin; Female; Humans; Male; Middle Aged; Pancreatic Neoplasms; Prospective Studies